(untitled) (Indian Journal of Arid Horticulture, 2025)
The nutritive value of indigenous fruits (11), green leafy vegetables (12), other vegetables (11) and roots and tubers (8) of western India were analysed in terms of protein, fat, fiber, ash, carbohydrates and energy. The study concluded that the different indigenous fruits and vegetables consumed in tribal areas are rich source of protein and fat and may be used in daily diet. Hence these indigenous fruits and vegetable may be recommended to achieve sustainable food and nutritional security.